Agile web development with Rails - Thomas, Dave; Heinemeier Hansson, David (The Pragmatic Bookshelf, 2007)
Rails is a new approach to web-based application development that enables developers to create full-featured, sophisticated web-based applications using less code and less effort. Now programmers can get the job done right and still leave work on time. The book has been updated to take advantage of all the new Rails 1.2 features. The sample application uses migrations, Ajax, features a REST interface, and illustrates new Rails features. There are new chapters on migrations, active support, active record, and action controller (including the new resources-based routing). The Web 2.0 and deployment chapters have been completely rewritten to reflect the latest thinking. Now, you can learn which environments are best for your style application, and see how Capistrano makes managing your site simple. All the remaining chapters have been extensively updated. Finally, hundreds of comments from readers of the first edition have been incorporated, making this book simply the best available.
Keywords: Ruby (Computer program language) -- Handbooks, manuals, etc; Web site development -- Handbooks, manuals, etc; Softwareentwicklung; Ruby on Rails; Internet